The Auschwitz Concentration Camp : history, biographies, remembrance - Webb, Chris (Ibidem-Verlag, 2018)
This book provides a chronological account of the Auschwitz concentration camp from the camp's beginning in 1940 right up to its liberation in January 1945, and beyond. Chris Webb manages to find a balance between detailing the sufferings of the victims and the actions, characters, and fates of the perpetrators. He gives, in a concise form, a thorough and deeply disturbing overview of all aspects of Auschwitz and its many satellite camps. In addition, the book contains a vast collection of photographs and documents, some of them never shown in public before. It ends with the 2017 recollections by students who visited Auschwitz from Teesside University.